ANALISIS BUTIR SOAL UJIAN AKHIR SEMESTER MATA KULIAH PENGANTAR PENYUNTINGAN - Utami, Santi Pratiwi T; Juidah, Imas; Muharudin, Eko; Syam, Suhendi; Yuda, Ramadhan Kusuma; Sumarwati (Universitas Wiralodra, 2021)
This study aims to describe the quality of the odd semester final exam items for the Introduction to Editing course for the 2020/2021 academic year at the Indonesian Literature Program, Universitas Negeri Semarang. This research is a quantitative research with descriptive method. The research subjects were 60 students. Data collection techniques were carried out by documenting. Quantitative data analysis based on level of difficulty, discriminating power, quality of distractors, validity, and reliability with 100 questions. The results of the analysis show that the quality of the odd semester final exam items in the Introduction to Editing course has a moderate level of difficulty, sufficient discriminating power, and very good distracting qualities. In addition, there are 68 valid items and 0.78 reliability in the high category. The conclusion of the study is that the odd semester final exam items for the Introduction to Editing subject need to be revised to improve the quality of the items.